Cerebral Protection During Catheter Ablation of Ventricular Tachycardia in Patients With Ischemic Heart Disease. Issue 13 (3rd July 2018) - Heeger, Christian‐Hendrik; Metzner, Andreas; Schlüter, Michael; Rillig, Andreas; Mathew, Shibu; Tilz, Roland Richard; Wohlmuth, Peter; Romero, Maria E.; Virmani, Renu; Fink, Thomas; Reissmann, Bruno; Lemes, Christine; et al.
Abstract : Background: Catheter ablation of ventricular tachycardia (VT) is associated with the risk of cerebral embolism. The origin of periprocedural brain embolism in the setting of VT ablation is often unknown and strategies to avoid it are sparse. The aim of this study was to assess the safety and feasibility of an endovascular 2‐filter‐based cerebral protection system (CPS) in left ventricular VT ablation procedures in patients with ischemic heart disease. Furthermore, histopathological correlates of periprocedural embolization were investigated. Methods and Results: In this pilot study, 11 patients with ischemic heart disease and sustained VT underwent left ventricular catheter ablation under CPS surveillance. The placement of the CPS was conducted before the ablation procedure via the right radial artery. The VT ablation procedure was performed via a combined transaortic and transseptal approach. All VTs were successfully ablated. Placement and retrieval of the CPS was successful and safe in all cases. No periprocedural complications related to the CPS were observed and no periprocedural transient ischemic attack or stroke occurred. Debris captured by the CPS was detected in all patients. Histology revealed that acute thrombus was the most common type of debris (91%), followed by arterial wall tissue (73%) and foreign material (55%). Less frequently found were myocardium (27%), calcification (9%), necrotic core (9%), and valve tissue (9%). Conclusions: Cerebral protection during VT ablation seems to be safe and feasible. Ablation procedures of VT are associated with embolization of embolic debris, which was found in every patient.